ADVANTAGES OF A SINGLE FREQUENCY NETWORK COMPARED TO MULTIPLE FREQUENCY NETWORKS - Blanco Orta, Jorge Luis; Guerra Martínez, María del Carmen; Martínez Gómez, Reinier (Telemática, 2020)
In this article, a study is made on Single Frequency Networks (SFN) and their influence on television systems that currently exist. A comparison is made with the technology used in analog and digital television systems, as is the case with Multiple Frequency Networks (MFN). Defining the SFN as a set of transmitting devices in charge of propagating the same information simultaneously and synchronized using the same channel. This will be possible thanks to the insertion of the guard interval in the Orthogonal Frequency Division Multiplexing (OFDM) signal, which will allow the echoes or multipaths that come from the different transmitters to be treated in such a way that the signal can be reconstructed in the receiver. In addition, some of the most widely used implementations in the world using SFNs are discussed, such as the standard of Integration of Digital Transmission Services - Territorial of Brazil (ISDB-Tb) and Digital Terrestrial Television (DTT), with the purpose of improving the transmission in some areas, where there is not a good reception of the transmitted signal, so that a more efficient use of the radio spectrum is made, maintaining a coverage similar to that provided by the MFN.